The crime of tax fraud in Spain (Ius Novum, 2018)
The paper analyses essential features of the crime of tax fraud laid down in Article 305 of the Spanish Criminal Code. The fraud consists in tax evasion or use of undue tax exemptions. The important element of liability for this crime is the legal-tax relation between the perpetrator and the tax administration. The author emphasizes that it is not necessary to deceive the tax administration; it is sufficient not to fulfil the formal duty, which materialises in hiding or disfiguring the tax base, making the determination of tax impossible. The analysis covers also perpetration, co-perpetration, necessary co-perpetration, aiding and abetting, defrauded tax amount, administrative calculation of the due amount and its judicial determination, illegal increment in property in the context of liability for tax fraud, illegal income, as well as the liability of legal counsels, tax advisors or accountants.
Keywords: tax advisors; tax fraud; fiscal penal law; perpetration and aiding